Bacterial endosymbionts influence host sexuality and reveal reproductive genes of early divergent fungi. Issue 1 (December 2017) - Mondo, Stephen; Lastovetsky, Olga; Gaspar, Maria; Schwardt, Nicole; Barber, Colin; Riley, Robert; Sun, Hui; Grigoriev, Igor; Pawlowska, Teresa
Abstract Many heritable mutualisms, in which beneficial symbionts are transmitted vertically between host generations, originate as antagonisms with parasite dispersal constrained by the host. Only after the parasite gains control over its transmission is the symbiosis expected to transition from antagonism to mutualism. Here, we explore this prediction in the mutualism between the fungusRhizopus microsporus (Rm, Mucoromycotina) and a beta-proteobacteriumBurkholderia, which controls host asexual reproduction. We show that reproductive addiction ofRm to endobacteria extends to mating, and is mediated by the symbiont gaining transcriptional control of the fungalras2 gene, which encodes a GTPase central to fungal reproductive development. We also discover candidate G-protein-coupled receptors for the perception of trisporic acids, mating pheromones unique to Mucoromycotina. Our results demonstrate that regulating host asexual proliferation and modifying its sexual reproduction are sufficient for the symbiont's control of its own transmission, needed for antagonism-to-mutualism transition in heritable symbioses. These properties establish theRm-Burkholderia symbiosis as a powerful system for identifying reproductive genes in Mucoromycotina. Cells of the fungusRhizopus microsporus containBurkholderia endobacteria that control its asexual reproduction. Here, the authors show that the endobacteria also mediate mating of the fungal host by modulating expression of a GTPase central to fungal reproductive development.